2012
DOI: 10.5005/jp-journals-10024-1147
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cells Attachment after Root Conditioning and PRP Application: An in vitro Study

Abstract: Aim: Root conditioning is aimed at smear layer removal and at dental matrix collagen exposure, which may promote periodontal regeneration. This in vitro study assessed smear layer removal, collagen fiber exposure and the influence of PRP (platelet-rich plasma) application on adhesion of blood cells to the root surface using scanning electron microscopy (SEM). Materials and methods:Scaled root samples (n = 160) were set in five groups and conditioned with: group I -control group (saline solution); group II (EDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The dried specimens were mounted on the stubs of a scanning electron microscope and coated with gold and palladium in a sputter coating machine (Bal-Tec SCD 050; Bal-Tec, Los Angeles, USA). The samples were again stored in a desiccator jar at room temperature for 3 days, 9 and then examined under the SEM for the presence of a clot. The collected samples were analyzed using the HITACHI S-3700N SEM (Hitachi High-Tech, Hitachinaka, Japan) with a working distance (WD) of 13.3-16.4 mm, 15.0 kV, and magnification of ×2,000 and ×5,000.…”
Section: Preparation Of Dentinal Blocks For Semmentioning
confidence: 99%
“…The dried specimens were mounted on the stubs of a scanning electron microscope and coated with gold and palladium in a sputter coating machine (Bal-Tec SCD 050; Bal-Tec, Los Angeles, USA). The samples were again stored in a desiccator jar at room temperature for 3 days, 9 and then examined under the SEM for the presence of a clot. The collected samples were analyzed using the HITACHI S-3700N SEM (Hitachi High-Tech, Hitachinaka, Japan) with a working distance (WD) of 13.3-16.4 mm, 15.0 kV, and magnification of ×2,000 and ×5,000.…”
Section: Preparation Of Dentinal Blocks For Semmentioning
confidence: 99%
“…17 The idea behind PAR4-AP coating stemmed from the observation that the epithelium-to-tooth attachment via basal lamina begins with the activated platelet aggregation on a cleaned root surface after periodontal treatment. 18,19 Previous in vitro studies revealed that basal lamina-mediated epithelial cell attachment was successfully achieved via platelet aggregation, 16,20 and bacterial colonization was effectively suppressed at the interface between the PAR4-AP-coated titanium surface and epithelium. 21 It was also found that perpendicular alignment of the collagen fibers (pCol) to the titanium surface could be achieved by means of electrophoretic fusion (EPF).…”
Section: Introductionmentioning
confidence: 99%